Mental and physical health conditions in people with intellectual disabilities: Comparing local and national data. (29th December 2019) - Perera, Bhathika; Audi, Salma; Solomou, Solomis; Courtenay, Ken; Ramsay, Hugh
Accessible summary: People with intellectual disability have multiple health problems. People with intellectual disability have more physical and mental health conditions than people without intellectual disabilities. People with intellectual disability may need more health checks due to increased prevalence of physical and mental illnesses. More studies are needed to understand what interventions are effective to reduce health problems in people with intellectual disability. Abstract: Background: Studies have reported increased prevalence of physical and mental health conditions in people with intellectual disabilities (ID) compared to people without intellectual disabilities. However, there are no studies looking into specific health conditions at a national level and comparing with areas that are socio‐economically disadvantaged (e.g. low income and low education attainment). This study examines and compares the prevalence of physical and mental health morbidity in people with and without intellectual disabilities at a local and national level in the UK. Method: This study was an anecdotal analysis of physical and mental health data and annual health check‐up for England (national), London (regional) and Haringey (inner‐city borough of London) in 2016/17 using data from the NHS Digital database. Results: Patterns of mental and physical conditions for people with and without intellectual disabilities were similar across Haringey, London and England data. Severe mental illness was more prevalent among people with intellectual disabilities compared to non‐intellectual disability peers. This further increased in the inner‐city London borough for the intellectual disability group. Certain physical health conditions were also more prevalent in people with intellectual disabilities. Certain activities such as monitoring blood pressure, recording body mass index and checking HbA1C were better in people with intellectual disabilities. Uptake of annual health checks for people with intellectual disabilities remained around 50%. Discussion: This study further highlights the increased prevalence of mental and physical disorders in people with intellectual disabilities compared to people without intellectual disabilities. Further increased risk of mental disorders in an inner London borough compared to national data aligns with existing literature that highlights the negative impact of socio‐economic deprivation on mental and physical health. Further studies are needed to assess the health and social care measures that can reduce the physical and mental health morbidity in people with intellectual disabilities.